Stik Siwalan: Inovasi Olahan Buah Siwalan sebagai Produk Lokal Bernilai Tambah di Desa Kowang - Ilmiyah, Qomariyatul; Ghoni, Abdul; Suciani, Indah; Marwan, Amiruddin; Al-Jufri, Salim; Lestari, Sri; Tasbihah, Ahya Lailah; Nurhayati, Rofiah; Sari, Neni Novita; Munadhiroh, Munadhiroh; Achmad, Hilmy Naufal Bani; Rosyida, Ela; Alfadhilah, Jauharotina; Shodiqoh, Mira (Pakis Journal Institute, 2025)
The Community Service Program (KKN) based on Asset Based Community Development (ABCD) in Kowang Village, Semanding District, Tuban, utilizes the local potential of siwalan fruit (Borassus flabellifer), which has so far only been consumed fresh with limited economic value. The perishable nature of siwalan makes large-scale marketing difficult, thus requiring processed innovations that are more durable and value-added. Through collaboration between students and the community, a product innovation was developed in the form of siwalan sticks, a crispy snack made from siwalan flesh mixed with flour and simple seasonings. The stick form was chosen because it is practical, favored by various groups, easy to produce with household equipment, and has the potential to be marketed as a Tuban specialty souvenir. The program activities included production socialization, training in hygienic processing and packaging, digital marketing training, and halal certification education to improve legality and consumer trust. The results showed improved skills of PKK women in producing siwalan sticks, the emergence of home-based business opportunities, and increased awareness of quality standards and product legality. This innovation demonstrates that the ABCD approach can optimize local potential while strengthening cultural identity through distinctive culinary products that are economically valuable and sustainable.